EXPLORING THE RELATIONSHIP BETWEEN ASPIRATIONS AND EDUCATIONAL EXPERIENCES AMONG QUEBEC YOUTH IN RESIDENTIAL CARE WHO ARE AT THE EDGE OF TRANSITION TO ADULTHOOD - Marion, Elodie; Rozefort, Annika; Tchuindibi, Laurence (International Journal of Child, Youth and Family Studies, 2023)
This article explores the development of aspirations among young people in residential care who are on the cusp of adulthood, and the relationship between their aspirations and their educational experience. We examine the specific aspirations of young people, what shapes those aspirations, and how they interact with their educational experience. This article is based on a qualitative study that aimed to better understand the educational experience of young people in residential care in the Canadian province of Quebec. Biographical interviews were conducted with 35 young people aged 14 to 18. Our analysis demonstrates that, while many seem quite able to project themselves into the future, some appear to see their placement situation and its accompanying uncertainty as an obstacle to doing so. It also suggests that educational and professional aspirations can transform young people’s educational experiences and the meaning that they attribute to formal education, as well as influence their intention to pursue further education. Finally, our results offer a critical look at how youth construct their aspirations, and demonstrate the importance of providing conditions that allow and encourage youth in residential care to develop and pursue varied aspirations.